CUANTIFICAREA UNOR ANTIOXIDANŢI CU CAPACITĂŢI ANTIRADICALICE - Lidia CALMUŢCHI; Eugenia MELENTIEV (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii)
The article presents the problems of formation of free radicals of oxygen in humans and their negative impact on his health. Active forms of oxygen lead to such diseases as a cancer, diabetes, a heart attack, a stroke, diseases of nervous and immune system, are the reason of aging of an organism. Antioxidants are those substances which are able to block the free radical reaction. Such substances are enzymes, vitamins, bioflavonoids, sulfur-containing amino acids, trace elements, etc. As a result of spectrophotometric studies of bioflavonoids, the fraction of polyphenols in red and white wines using the reagent Folin–Ciocâlteu found enough of them, which corresponds to the norm, both in red and in white wines, however in red wines it means more antioxidant ability and its better.